(untitled) (Altre Modernità, 2022)
The article analyses the rise and the development of Ploshad Peremen, Minsk, during the Belarusian protests, which have begun in August 2020. Ploshad Peremen is a space of resistance, a gathering place for alternative forms of protest. Located in a courtyard in ulitsa Chervyakova, it appeared after Kirill Galanov and Vladislav Sokolovsky’s subversive gesture: the two Djs, at an official pro-Lukashenko concert, played Kino’s “Peremen”, an anthem for change, which got them arrested. In Ploshad Peremen the protest is expressed through dancing nights, theatrical performances, paintings, street art and especially concerts. The meaning and the subversive value of four recurring songs are considered: Kino’s “Peremen”, wrote by Viktor Tsoj in 1989, “Steny ruchnut”, Russian version of the anthem of the Solidarity, composed by Jacek Kaczmarsky in 1980, “Vychodi gulyat” by the Russian hip-hop band Kasta, and “My ne narodets” by the Belarusian rock band Tor Band, released in June. The original meaning of the four songs is explained and the reasons of their relevance in the Belarusian protests are pointed out. Moreover, the article emphasizes the role of Telegram as new communication channel, pivotal to the organization of the protests.